Ensuring Psychosocial Interventions Align with Rights-Based Mental Healthcare in India - Jyoti Tripathy; Deepanjali Tripathy (Nusantara Society Lab, 2025)
The Mental Healthcare Act (MHCA), 2017 marked a paradigm shift in India’s mental health landscape by reframing mental illness through the lens of rights, dignity, and person-centered care. While the Act enshrines psychosocial interventions as an essential component of treatment, implementation remains uneven, hindered by workforce shortages, systemic biomedical bias, financial inaccessibility, and weak ethical oversight. This commentary critically examines the interface between MHCA 2017 and psychosocial care, highlighting gaps in service delivery, the persistence of harmful practices such as conversion therapy, and the neglect of adverse outcomes in psychotherapy. It argues that without structural reforms including integration of the National Commission for Allied and Healthcare Professions Act, 2021, expanded insurance coverage, stronger accountability mechanisms, and recognition of allied professionals psychosocial interventions risk remaining marginalized. The article emphasizes the urgent need for rights-based, culturally sensitive, and ethically sound practices to realize the transformative vision of MHCA 2017. Strengthening psychosocial care is not ancillary but central to building a mental health system grounded in equity, recovery, and human dignity.